A single‐institution retrospective study of causes of prolonged prothrombin time and activated partial thromboplastin time in the outpatient setting. (5th October 2021) - Hazim, Antonious Z.; Ruan, Gordon J.; Khodadadi, Ryan B.; Slusser, Joshua P.; Marshall, Ariela L.; Pruthi, Rajiv K.
Abstract: Introduction: An algorithmic approach, termed the prolonged clot time profile (PROCT), consisting of initial screening with prothrombin time (PT) and activated partial thromboplastin time (aPTT), reflexive mixing studies if indicated, and follow‐up assays depending on initial testing results, offers an efficient approach to delineate the etiology of a prolonged PT/aPTT. Herein, we present the outcomes of the PROCT in the outpatient setting. Methods: In this retrospective study, we reviewed medical records of consecutive outpatients who had prolonged PT and/or aPTT noted in the routine coagulation laboratory and who had PROCT ordered in our institutional Special Coagulation Laboratory between 2010 and 2017. Results: One hundred and six patients, median age 55 years (IQR 30‐67), met our study criteria. Twenty‐nine patients had normal PT/aPTT, while 77 had persistent abnormalities and underwent reflexive testing. A prolonged PT, aPTT, or PT and aPTT was noted in 27 (35%), 27 (35%), and 23 (30%) respectively. Forty‐nine (64%) had an acquired condition, 17 (22%) had a congenital condition, 7 (9%) had unclear etiology, and 4 (5%) were the result of laboratory artifact. The most common known cause of an isolated prolonged PT in our study was vitamin K deficiency in 8 (10%), the most common cause of an isolated prolonged aPTT was lupus anticoagulant in 4 (5%), and the most common cause of prolonged PT and aPTT was liver disease in 11 (14%). Conclusion: Prolonged PT/aPTT have a wide range of causes, including artifactual prolongation or abnormalities in secondary hemostasis due to both inherited and acquired conditions.